R biblioshiny application to explore sustainability research trends in Islamic finance: scientometric research - Widaryanti Widaryanti; Wan Amalina Wan Abdullah; Riana Sitawati; Rudika Harminingtyas (Journal of Islamic Accounting and Finance Research, 2025)
Purpose - This study aims to identify research trends on sustainability in Islamic finance as published by leading journals. Method - A total of 54 indexed publications was analyzed using the R Bibliometric application to generate a bibliometric map of sustainability in Islamic finance.   Result - The analysis shows a consistent annual increase in sustainability-related Islamic finance research, with the Isra International Journal of Islamic Finance being the most productive journal and Hassan MK as a prominent contributor.  Keyword analysis highlights “Islamism” and “sustainability” as dominant themes. Despite growth, research gaps remain that warrant further investigation. Implication - This study synthesizes existing research and identifies gaps, providing insights for scholars, policymakers, and practitioners to enhance the integration of sustainability in Islamic finance. Originality - This study introduces a novel application of Biblioshiny to explore sustainability literature in Islamic finance. Although Islamic finance is a broad topic, the specific focus on sustainability provides unique value, especially given the increasing attention to sustainability issues in various financial sectors.